Establishing the Hardboiled Fiction as a Literary Landmark in Dashiell Hammett’s Red Harvest - Khadeeja Saeed Ismail (Zanco Journal of Humanity Sciences)
In spite of the existence of a great number of hardboiled detective novels in American literature, Dashiell Hammett’s Red Harvest (1929) is regarded as a work beyond that of many others. The novel is Hammett’s first detective tale and the first crime fiction that found out a new subgenre in crime literature. Critics refer to it as a literary milestone, due to the writer’s realism, which was entirely unlike the way other writers wrote. This study argues that in addition to its realism the significance of the work is ascribed to Hammett’s urban setting, colorful characterization of the detective, foreboding narration, and the writer’s unusual notion of gender roles. The paper concludes that by the presentation of the true American world, penetrating through its affairs, and anticipating the consequences, Hammett detached British and American crime fiction, which was seen as one whole previously.